Impact of Cannabis Use on Least Pain Scores Among African American and White Patients with Cancer Pain: A Moderation Analysis - Meghani SH (Dove Medical Press, 2021)
Salimah H Meghani,1,2 Ryan Quinn,1 Rebecca Ashare,3,4 Kristin Levoy,1,5,6 Brooke Worster,7 Mary Naylor,1,2 Jesse Chittams,1 Martin Cheatle8 1Department of Biobehavioral Health Sciences, NewCourtland Center for Transitions and Health, School of Nursing, University of Pennsylvania, Philadelphia, PA, USA; 2Leonard Davis Institute for Health Economics, University of Pennsylvania, Philadelphia, PA, USA; 3Department of Psychiatry, Perelman School of Medicine, University of Pennsylvania, Philadelphia, PA, USA; 4Department of Psychology, State University of New York at Buffalo, Buffalo, NY, USA; 5Department of Community and Health Systems, School of Nursing, Indiana University, Indianapolis, IN, USA; 6Center for Aging Research, Regenstrief Institute, Indianapolis, IN, USA; 7Department of Medical Oncology, Sidney Kimmel Cancer Center, Thomas Jefferson University, Philadelphia, PA, USA; 8Department of Psychiatry and Anesthesiology, Perelman School of Medicine, University of Pennsylvania, Philadelphia, PA, USACorrespondence: Salimah H MeghaniDepartment of Biobehavioral Health Sciences, NewCourtland Center for Transitions and Health, Leonard Davis Institute for Health Economics, University of Pennsylvania, Philadelphia, PA, USATel +215 573-7128Email meghanis@nursing.upenn.eduIntroduction: Based on many published reports, African American patients with cancer experience higher pain severity scores and lower pain relief than White patients. This disparity results from undertreatment of pain and is compounded by low adherence to prescribed non-opioid and opioid analgesics among African American patients with cancer. While nearly one in four patients use cannabis to manage cancer-related symptoms, less is known about how cannabis use influences pain relief in this patient population.Methods: This study is based on preliminary data from an ongoing study of longitudinal outcomes of opioid therapy among African American and White patients with cancer. Linear mixed-effects models were utilized to assess the interaction of race and cannabis use on pain relief using “least pain” item scores from the Brief Pain Inventory (BPI) averaged across three time points. Models were adjusted for sociodemographic and clinical variables.Results: This analysis included 136 patients (49 African American, 87 White). Overall, 30.1% of the sample reported cannabis use for cancer pain. The mean “least pain” score on BPI was 3.3 (SD=2.42) on a scale of 0– 10. African American patients had a mean “least pain” score 1.32± 0.48 units higher (indicating lower pain relief) than White patients (p=0.006). Cannabis use did not have a significant main effect (p=0.28). However, cannabis use was a significant moderator of the relationship between race and “least pain” (p=0.03). In the absence of cannabis use, African Americans reported higher “least pain” scores compared to Whites (mean difference=1.631± 0.5, p=0.001). However, this disparity was no longer observed in African American patients reporting cannabis use (mean “least pain” difference=0.587± 0.59, p=0.32).Conclusion: These findings point to the possible role of cannabis in cancer pain management and its potential to reduce racial disparities. These findings are preliminary and further research into the role of cannabis in cancer pain outcomes is needed.Keywords: pain, cancer pain, pain relief, pain disparities, cannabis